The Contribution of Women Entrepreneurs to Economic Decision-Making within Households in Semayan Village, Praya District, Central Lombok Regency - Baiq Nora Elena Dwi Putri; Luluk Fadliyanti; Vici Handalusia Husni (Journal of Finance, Economics and Business, 2026)
This study aims to examine the contribution of women entrepreneurs to household economic decision-making, the influence of women entrepreneurs’ bargaining power on household economic decision-making, and the factors affecting household economic decision-making in Semayan Village, Praya District, Central Lombok Regency. This research employs a qualitative approach using a case study method. Data were collected through observation, in-depth interviews, and documentation. Informants were selected using purposive sampling, with primary data as the main source. Data validity was ensured through source triangulation, methodological tringulation and time triangulation. The findings reveal that women’s contributions as entrepreneurs influence household economic decision-making and strengthen their bargaining power within the family. Decision-making areas affected include household expenditure management, children’s education, as well as business and investment decisions. However, the level of influence is shaped by intra-household relations, income levels, and prevailing social norms within the community.